Millennials' Interests and Perceptions of Cryptocurency, Stocks, Gold and Forex as Investment Instruments in the Future - Mira Maryani; Romulo Sinabutar (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out the interests and perceptions of millennials towards investment instruments in future financial planning and provide some brief explanations of the forms of investment. Along with the development of technology today many conveniences that can be felt by the community, especially the millennial generation to invest. The study used quantitative approach methods of online questionnaire filling in to 50 respondents. And getting the results of basic knowledge of capital markets greatly affects the interests and perceptions of millennials in making investment instruments, while risk preferences negatively affect interest and perception in choosing investment instruments, meaning that if risk preferences increase then investment interest and perception decreases and vice versa.